The Economics of Spatial Mobility: Theory and Evidence Using Smartphone Data - Yuhei Miyauchi; Kentaro Nakajima; Stephen J Redding (The Quarterly Journal of Economics, 2025)
ABSTRACT We develop a tractable quantitative framework for modeling the rich patterns of spatial mobility observed in smartphone data. We show that travel is frequently undertaken as part of a travel itinerary, defined as a journey starting and ending at home that can include more than one intermediate stop on a given day. We show that these travel itineraries provide microfoundations for consumption externalities and generate both complementarity and substitutability between locations. We show that the consumption externalities implied by travel itineraries are central to matching quasi-experimental evidence from the shift to working from home. We find that these consumption externalities are key drivers of the agglomeration of economic activity in central cities and shape the relative welfare gains from alternative transport improvements in favor of investments in central cities.